My Name is February - Ferrus, Diana (New Agenda: SA Journal of Social and Economic Policy, 2025)
Diane Ferrus is a poet, writer, performance artist, activist, founder member of Bush Poets, the Afrikaans Writers Association (Afrikaanse Skrywersvereniging) and Women in Xchains. She is a member of the Women’s Education and Artistic Voice Expression (WEAVE), played an instrumental role in the repatriation of Sarah Baartman’s remains from France to South Africa and was a recipient of the Minister’s Award for Women. Her work has been published in various collections and some serve as prescribed texts for high school learners. She worked for 25 years at the University of the Western Cape until she retired in 2016. She has completed a postgraduate degree in Women’s and Gender Studies.Diane performed this poem at the ‘Unbroken Spirits: Concert for Humanity’ that formed part of the Living Rights Festival. She has graciously given New Agenda permission to publish this poem.